Prevalence of Aspergillus in the phyllosphere of Ocimum sanctum - Sharma, Kavita (Journal of Phytology, 2012)
Leaf surface is the platform of the numerous fungal spores present in the air. During suitable microhabitat these spores are settled down on this having platform and try to colonised. After settle down fungal spores, a triangular relationship appears among the micro-organisms, leaf surface and the environment. The present paper deals with the study of leaf surface mycoflora of Ocimum sanctum with the help of petriplate method in one year. Ocimum sanctum plant grown in hindu families in India. 447 colonies of 33 fungal species belonging to 18 genera of fungi were isolated during the present investigation from the leaf surface mycoflora of Ocimum sanctum. Out of 447 colonies, 212 colonies of 8 species of Aspergillus observed during the investigation period i.e. A. flavus, A. fumigatus, A.luchensis, A.nidulans, A.niger, A.sulphureus, A.sydowii and A.terreus. It was also observed that A.niger (12.52%) showed maximum percentage contribution and most frequent fungi among all 33 fungal species. During the study, it was also recorded that A.niger and A. Fumigatus were observed throughout the year. The effect of leaf exudates and leaf tissue sap of Ocimum sanctum plant on spore germination of Aspergillus species was also observed. The spore of Aspergillus failed to germinate on both sap as well as exudates. Species of Aspergillus are important medically and commercially. Some Aspergillus species cause serious disease in humans and animals. The most common causing pathogenic species are Aspergillus fumigatus and Aspergillus flavus.